[Imported malaria in Tunisia]. - (:unkn) unknown (My University, 1998)
Thanks to the national programme of malaria eradication carried out between 1968 and 1972, there has been no active transmission of the parasitosis in Tunisia since the last indigenous case in 1979. Since 1980, with the increase in international exchanges especially with sub-Saharian countries, only imported cases of malaria have been reported in Tunisia. A retrospective and thorough survey of malaria cases diagnosed in the laboratory of parasitology of the Pasteur Institute in Tunis from 1980 to 1995 determined the epidemiological characteristics of this imported parasitosis. All in all, during the sixteen years following eradication, 245 cases were registered. The majority of cases (86.2%) was diagnosed by a systematic control of groups at risk within the national programme of malaria eradication. The remaining 13.8% cases sought medical advice when clinical symptoms appeared after their return from endemic countries. The population most affected by imported malaria were men (sex-ratio: 6.8) aged between 20 and 40 years (76% of cases); 38% were Tunisians having sojourned in an endemic country, essentially students from sub-Saharian Africa. The presumed country of contamination was African in 92.7% of the cases. Entrance into Tunisia by patients was mainly by air; 4% of the registered cases had come by land from Algeria. Sound knowledge of the epidemiological characteristics of imported malaria would make for a better follow-up of the affected population and thus reduce the probability of repeated transmission.
Keywords: African Research